Application of Physiologically Based Pharmacokinetic (PBPK) Modeling to Support Dose Selection: Report of an FDA Public Workshop on PBPK. (17th April 2015) - Wagner, C; Zhao, P; Pan, Y; Hsu, V; Grillo, J; Huang, SM; Sinha, V
<x xml:space="preserve">Abstract</x> The US Food and Drug Administration (FDA) public workshop, entitled "Application of Physiologically‐based Pharmacokinetic (PBPK) Modeling to Support Dose Selection focused on the role of PBPK in drug development and regulation. Representatives from industry, academia, and regulatory agencies discussed the issues within plenary and panel discussions. This report summarizes the discussions and provides current perspectives on the application of PBPK in different areas, including its utility, predictive performance, and reporting for regulatory submissions.